John Milton’s ‘Chaotic’ Satan - Tomasz Jabłoński (Anglica. An International Journal of English Studies)
This article investigates the affi nity between the characters of Satan and Chaos in John Milton’s Paradise Lost. My aim is to show the connections between those characters that appear surprising in the light of Milton’s professed theodicy. On closer inspection certain contradictions become manifest, which may enable analysis of the epic not usually advocated by Miltonic criticism. I propose a fusion of more or less customary Paradise Lost’s criticism with 20th century’s existential philosophy exemplified by Nicolai Berdjaev